WORK DISCIPLINE, LEADERSHIP STYLE, TRAINING AND EMPLOYEE PERFORMANCE AT BAGHDAD HOSPITAL - farqad; Abd Rahman Kadir (Scientia Integritas Utama, 2023)
This study aims to describe the description of work discipline, leadership style, training and employee performance at Baghdad Hospital. This research model uses a qualitative descriptive research type through a literature review study approach using several sources selected based on predetermined inclusion and exclusion criteria. researcher. The results of the analysis show the overall performance of employees, and the impact received by the company is the result of employee performance in accordance with the wishes and conditions of the company. The influence of leadership style and discipline on employee performance is based on the points used by the company as parameters to achieve company targets, namely quality, quantity, time savings and cost efficiency.